2019
DOI: 10.3389/fonc.2019.01103
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA AFAP1-AS1 Supresses miR-139-5p and Promotes Cell Proliferation and Chemotherapy Resistance of Non-small Cell Lung Cancer by Competitively Upregulating RRM2

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related death worldwide. This study aims to understand the underlying mechanism of lncRNA, actin filament-associated protein 1 antisense RNA 1(AFAP1-AS1) in mediating chemotherapeutic resistance in NSCLC. The levels of AFAP1-AS1 in NSCLC tissues and cells were determined using RT-PCR. The protein levels of RRM2, EGFR, and p-AKT were analyzed using Western blotting. Binding between AFAP1-AS1 and miR-139-5p was confirmed using dual luciferase repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 47 publications
3
75
1
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) were reported to contribute the initiation and development of cancers by our and other groups (Bautista et al, 2018 ; Chang et al, 2018 ; Zhao et al, 2018 ; Huang et al, 2019 ; Li et al, 2020 ). HOX transcript antisense RNA (HOTAIR) enhances lung cancer cell invasion and motility (Zhao et al, 2014a ).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Long non-coding RNAs (lncRNAs) were reported to contribute the initiation and development of cancers by our and other groups (Bautista et al, 2018 ; Chang et al, 2018 ; Zhao et al, 2018 ; Huang et al, 2019 ; Li et al, 2020 ). HOX transcript antisense RNA (HOTAIR) enhances lung cancer cell invasion and motility (Zhao et al, 2014a ).…”
Section: Introductionmentioning
confidence: 84%
“…Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is considered a key marker of metastasis in lung cancer (Gutschner et al, 2013 ). The lncRNA actin filament-associated protein 1 antisense RNA 1 (AFAP1-AS1) promotes NSCLC tumorigenesis and chemoresistance (Yin et al, 2018 ; Huang et al, 2019 ). SBF2-AS1, an oncogenic lncRNA, increases NSCLC cell proliferation (Lv et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Souglakos' study revealed that the efficacy of docetaxel/gemcitabine in lung adenocarcinoma patients was associated with RRM2 mRNA expression from 42 patients 18 . Huang and colleagues studied 44 patient samples and found that the overexpression of RRM2 promoted proliferation, inhibited apoptosis, and increased the chemotherapy resistance of NSCLC cells through upregulating EGFR expression and AKT phosphorylation 17 . Recently, Yang's team worked on 30 patients and found that RRM2 was upregulated in NSCLC tumors and cell lines, leading to poor prognosis 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, RRM2 has also been involved in several ceRNA networks and its upregulation has been found to trigger cell proliferation, drug-resistance and tumor growth in LC [26,27]. Importantly, arti cial up-regulation of RRM2 in cells promoted cell viability, migration, invasion and resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 99%